Effect of pullulan active packaging, incorporated with silver nanoparticles, on cholesterol oxidation product concentrations in boiler meat during storage - Khan, Muhammad Jamshed; Mookiah, Saminathan; Subramaniam, Yashini; Ramiah, Suriya Kumari (Codon Publications, 2024)
Cholesterol oxidation products (COPs) in meat are thrombogenic, mutagenic, atherogenic, carcinogenic, angiotoxic, and cytotoxic, leading to serious health issues. The formation of COPs in meat is induced by oxidative rancidity due to poor meat processing and packaging techniques. Pullulan active packaging, incorporated with silver nanoparticles (AgNPs), is considered strong and biodegradable with characteristics, such as enhanced light, gas, and moisture barrier, that protect the oxidative rancidity of broiler meat. The current study was performed to determine the impact of pullulan active packaging (T1, T2, T3, and T4) on the formation of COPs in broiler meat during refrigerated storage (7 and 14 days). Pullulan active packaging significantly affected (P < 0.05) the concentrations of A-cholestane (0.63±0.10 ppm) and B-epoxy (0.59±0.33 ppm) COPs whereas A-cholestane (0.634±0.08 ppm) was affected significantly (P < 0.05) by the duration of refrigerated storage (0, 7, and 14 days). Broiler meat treated with pullulan active packaging presented a limited level of oxidative rancidity with minimum concentrations of COPs. The findings revealed that broiler meat treated with pullulan active packaging, incorporated with AgNPs, is safer than raw meat for shorter (7 days) and longer (14 days) storage periods at 4±1°C.